Spot urine samples compared with 24-h urine samples for estimating changes in urinary sodium and potassium excretion in the China Salt Substitute and Stroke Study. (10th October 2018) - Huang, Liping; Woodward, Mark; Stepien, Sandrine; Tian, Maoyi; Yin, Xuejun; Hao, Zhixin; Li, Zhifang; Sun, Jixin; Yu, Yan; Zhou, Bo; Zhao, Yi; Wu, Yangfeng; et al.
Abstract: Background: The capacity of spot urine samples for detecting changes in population sodium and potassium excretion is unclear. Methods: Changes in urinary sodium and potassium excretion, over a 6-month to 2-year interval, were measured from 24-h urine samples and estimated from spot urine samples using several published methods in 3270 Chinese. Additional estimates were made by multiplying individual spot sodium and potassium concentrations by a single estimated 24-h urine volume derived from external data. Results: The measured difference in 24-h urinary excretion between intervention and control groups was -0.35 g (95% CI: -0.68 to -0.02; P = 0.039) for sodium and 0.66 g (95% CI: 0.52 to 0.80; P < 0.001) for potassium, based upon 24-h urine samples. The corresponding estimates of sodium differences for the Tanaka (-0.06 g), Kawasaki (-0.09 g), Intersalt without potassium (-0.09 g) and Intersalt with potassium (-0.14 g) equations were all smaller and identified no reduction in sodium excretion (all P > 0.10). The estimates were -0.65 g for sodium and 1.11 g for potassium using individual spot urine concentrations and an externally derived standard urine volume (both P < 0.01). Conclusions: The published equations were unable to detect the differences in sodium excretion measured by 24-h urine samples. A method based upon spot urine electrolyte concentrations and a standard urine volume may offer an alternative approach to measuring differences in sodium and potassium excretion between population groups without requiring 24-h urine, but will need further investigation.